(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2013)
MEFV (Mediterranean Fever) gene is responsible for Familial Mediterranean Fever (FMF). Association of the MEFV gene mutations with clinical conditions other than FMF has recently been a subject of discussion where patients with other inflammatory conditions have also been diagnosed with FMF.